French Interpretations of Heidegger: An Exceptional Reception - Pettigrew, David; Raffoul, François (SUNY series in contemporary French thought, 2008)
"French Interpretations of Heidegger undertakes a philosophical engagement with the work of the most significant and creative figures involved in the reception of Heidegger in France. The essays address those thinkers who have been influenced by Heidegger's thought and have interpreted it in remarkable ways, including Levinas, Beaufret, Sartre, Merleau-Ponty, Foucault, Derrida, Deleuze, Nancy, Lacoue-Labarthe, Irigaray, Zarader, Greisch, and Dastur. The volume explores the extraordinary impact that Heidegger's thought has had on contemporary French philosophy, including such movements as existentialism, deconstruction, feminist theory, post-structuralism, and hermeneutics, and illustrates its impact on the American continental scene as well."--Jacket.
Keywords: Heidegger, Martin, 1889-1976; Philosophy, French; dept.phi; faculty_collection

Norbert wiener and the rise of information ethics - Bynum, T.W. (Information Technology and Moral Philosophy, 2008)
To live effectively is to live with adequate information. Thus, communication and control belong to the essence of man's inner life, even as they belong to his life in society. Norbert Wiener SCIENCE, TECHNOLOGY, AND ETHICS. Major scientific and technological innovations often have profound social and ethical effects. For example, in Europe during the sixteenth and seventeenth centuries, Copernicus, Newton, and other scientists developed a powerful new model of the universe. This stunning scientific achievement led to increased respect for science and for the power of human reasoning. During that same era, recently invented printing-press technology made it possible to spread knowledge far and wide across Europe, instead of leaving it, as before, in the hands of a privileged minority of scholars. Inspired by these scientific and technological achievements, philosophers, such as Hobbes, Locke, and Rousseau, re-examined human nature and the idea of a good society. They viewed human beings asrational agentscapable of thinking for themselves and acquiring knowledge through science and books. In addition, they interpreted society as a creation of informed, rational citizens working together throughsocial contracts. These philosophical developments laid foundations for ethical theories such as those of Bentham and Kant, and for political changes such as the American Revolution and the French Revolution. Today, after far-reaching scientific achievements in physics, biology, and cybernetics – and after recent technological advances in digital computing and information networks – philosophers are again rethinking the nature of human beings and of society. © Cambridge University Press 2008 and 2009.
Keywords: dept.phi

ICT and the tension between old and new: the human factor - Gorniak-Kocikowska, Krystyna (Journal of Information, Communication and Ethics in Society, 2008)
Purpose The purpose of this paper is to deepen the understanding of tensions between old and new in the emerging global society driven by information and communication technology (ICT); and to argue that creation of a theory of this society would contribute in the easing of these tensions. Design/methodology/approach The methods used in this paper are mostly analytical, descriptive, and qualitative. An analysis of the creation and development of ICT from a mathematical discipline of computer science to a universal tool and a driving force of the emerging global society, a development which is paralleled by the commercialization of ICT, is followed by two case studies illustrating the tensions between old and new and the role ICT plays in them. One case is centered on the challenges of traditional models of education by new, ICT-friendly approaches, like the Multiple Intelligences Theory; the other addresses tensions between old and new that in many societies presently take the form of tensions between local/national and global. Findings A claim is formed that the existing tensions between old and new are closely linked to the tensions between the two most common forms of society, inclusive (egalitarian) and exclusive (elitist). Originality/value The paper will help understand some of the reactions to the process of globalization. It can serve as a tool for assessment and prediction regarding this process. Lastly, the paper contains a justification of merit in the creation of a “grass root” theory of an ICT-driven global society built on a universally accepted ethical foundation. © 2008, Emerald Group Publishing Limited
Keywords: Communication technologies; Education; Ethics; Globalization; Information society; Language; dept.phi; peer-reviewed